Digital infrastructure for the learning health system : the foundation for continuous improvement in health care : workshop series summary - Grossmann, Claudia; Powers, Brian; McGinnis, J. Michael (Learning healthcare system series., 2011)
"Like many other industries, health care is increasingly turning to digital information and the use of electronic resources. The Institute of Medicine's Roundtable on Value & Science-Driven Health Care hosted three workshops to explore current efforts and opportunities to accelerate progress in improving health and health care with information technology systems."--Publisher's description